2016
DOI: 10.1186/s12958-016-0207-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of exosomal release in bovine endometrial intercaruncular stromal cells

Abstract: BackgroundCell-to-cell communication between the blastocyst and endometrium is critical for implantation. In recent years, evidence has emerged from studies in humans and several other animal species that exosomes are secreted from the endometrium and trophoblast cells and may play an important role in cell-to-cell communication maternal-fetal interface during early pregnancy. Exosomes are stable extracellular lipid bilayer vesicles that encapsulate proteins, miRNAs, and mRNAs, with the ability to deliver thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 62 publications
0
38
0
Order By: Relevance
“…Interestingly, proADAM10 and ADAM10f were also detected in culture media from CHO cells. Abundant ADAM10 has been found in exosomes of bovine endometrial stromal cells cultured at hypoxic conditions [ 42 ]. Thus, an exosomal contribution of ADAM10-CSF cannot be discounted.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, proADAM10 and ADAM10f were also detected in culture media from CHO cells. Abundant ADAM10 has been found in exosomes of bovine endometrial stromal cells cultured at hypoxic conditions [ 42 ]. Thus, an exosomal contribution of ADAM10-CSF cannot be discounted.…”
Section: Discussionmentioning
confidence: 99%
“…Existence of several metalloproteinases in endometrium‐derived exosomes has been reported (Greening et al, ; Koh et al, ). Importantly, it has been shown that the hormonal regulation of endometrial receptivity during the menstrual cycle can also affect the metalloproteinase content of the exosomes (Greening et al, ).…”
Section: Metalloproteinases Of Endometrium‐derived Exosomesmentioning
confidence: 96%
“…Although the existence and possible roles of uterine metalloproteinase have been documented (Chevronnay et al, ; Goldman & Shalev, ), the biological functions of exosome‐derived metalloproteinases in implantation have been poorly characterized. To date, proteomics and transcriptomics analyses have detected MMP‐14 (Greening et al, ) and ADAM‐10 (Greening et al, ; Koh et al, ) in endometrium‐derived exosomes. In the following sections, we describe the importance of these metalloproteinases in embryo implantation and their possible effects as members of endometrium‐derived exosomes on embryo‐endometrial interaction during the implantation period.…”
Section: Metalloproteinases Of Endometrium‐derived Exosomesmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of exosomes in reproductive system secretions also highlights their feasible roles in intercellular communications that are required in preconception and postconception; nevertheless, their alterations have recently been used as a marker for pregnancy and pathologies associated with pregnancy in humans .…”
Section: The Role Of Extracellular Vesicles In Female Physiological Pmentioning
confidence: 99%